2009
DOI: 10.3858/emm.2009.41.6.047
|View full text |Cite
|
Sign up to set email alerts
|

A reconstituted HDL containing V156K or R173C apoA-I exhibited anti-inflammatory activity in apo-E deficient mice and showed resistance to myeloperoxidase-mediated oxidation

Abstract: It has been hypothesized that blood infusion of reconstituted HDL (rHDL) is a possible therapeutic strategy for the treatment of coronary artery disese. To compare short-term anti-inflammatory activity of wildtype (WT) apoA-I and point mutants, each rHDL containing WT, V156K, or R173C was infused into apo-E deficient atherosclerotic mice. Each rHDL was injected via the tail vein at a dosage of 120 mg/kg of body weight in 0.4 ml of tris-buffered saline (TBS), and blood was then collected at 24 and 48 h post-inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…Recombinant V156K mutant behaved differently from the wild type in both lipid- free and lipid-bound states in vitro and in vivo (Cho et al, 2006(Cho et al, , 2007. V156K exhibited enhanced potent antioxidant and antiinflammatory activity, and an antiatherosclerotic effect (Cho and Kim, 2009) with different movement of the hinge domain of apoA-I as compared with wild type (Han et al, 2005). In addition, numerous clinical observations have shown that higher apoA-I serum concentrations result in lower cardiovascular risk (Walldius and Jungner, 2007).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recombinant V156K mutant behaved differently from the wild type in both lipid- free and lipid-bound states in vitro and in vivo (Cho et al, 2006(Cho et al, , 2007. V156K exhibited enhanced potent antioxidant and antiinflammatory activity, and an antiatherosclerotic effect (Cho and Kim, 2009) with different movement of the hinge domain of apoA-I as compared with wild type (Han et al, 2005). In addition, numerous clinical observations have shown that higher apoA-I serum concentrations result in lower cardiovascular risk (Walldius and Jungner, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…WT human apoA-I is composed of a single polypeptide chain of 243 amino acids and a principal protein component of HDL that is known to perform a crucial role in the reverse cholesterol transport pathway through its antioxidant and antiinflammatory activities (Barter et al, 2004;Ansell et al, 2005). A point mutant of apoA-I, V156K, showed unique structural and functional properties in vitro (Han et al, 2005), and V156K-rHDL has been shown to exert antioxidant effects in hypercholesterolemic C57BL=6 mice (Cho et al, 2006(Cho et al, , 2007 and antiatherosclerotic activity in apoE-deficient mice (Cho and Kim, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It demonstrated potent antioxidant activity and anti-inflammatory activity both in vivo and in vitro (20), as well as an in vivo anti-atherosclerotic effect (64,65). The pharmaceutical effects of V156K-rHDL were compared directly to WT-rHDL and R173C-rHDL.…”
Section: Blood Infusion Of Rhdl For Regressionmentioning
confidence: 99%
“…The most robust evidence for the atheroprotective function of HDL derives from the overexpression of apoA-I by transgenesis in mice and rabbits, which leads to a reduction in atherosclerosis, and the elimination of apoA-I expression in mouse models, which results in an accentuation of atherosclerosis. A few rare mutants of human apoA-I either enhance (ApoA-I Milano ) [5] or impair (ApoA-I Pisa or ApoA-I FIN ) [6] the function of apoA-I and HDL. Indeed, apoA-I Milano has been infused into patients to promote regression of atherosclerosis [7, 8].…”
Section: Introductionmentioning
confidence: 99%